Wolfram Alpha evaluates this integral numerically as

$$\int_0^{\infty} \frac{x^2}{\cosh^2 (x^2)} dx=0.379064 \dots$$

Its value is apparently

$$\frac{\sqrt{2}-2}{4} \sqrt{\pi}~ \zeta \left( \frac{1}{2} \right)=0.37906401072\dots$$

How would you solve this integral?

Obviously, we can make a substitution $t=x^2$

\begin{align} \int_0^{\infty} \frac{x^2}{\cosh^2 (x^2)} dx&=\frac{1}{2} \int_0^{\infty} \frac{\sqrt{t}}{\cosh^2 (t)} dt\\[10pt] &=\int_0^{\infty} \frac{\sqrt{t}}{\cosh (2t)+1} dt\\[10pt] &=\frac{1}{2 \sqrt{2}}\int_0^{\infty} \frac{\sqrt{u}}{\cosh (u)+1} du \end{align}

We could use geometric series since $\cosh (u) \geq 1$, but I don't know how it will help.

  • $\begingroup$ Maybe $\Gamma (s) \zeta (s)=\int_0^{\infty}\frac{u^{s-1}}{e^u-1}du$ helps. $\endgroup$
    – MrYouMath
    Jun 9 '16 at 22:01
  • $\begingroup$ It probably does, forgot about this, thank you $\endgroup$
    – Yuriy S
    Jun 9 '16 at 22:03

$$I=\frac{1}{2\sqrt{2}}\int_{0}^{+\infty}\frac{\sqrt{u}\,du}{1+\cosh(u)}=\frac{1}{\sqrt{2}}\int_{1}^{+\infty}\frac{\sqrt{\log v}}{(v+1)^2}\,dv=\frac{1}{\sqrt{2}}\int_{0}^{1}\frac{\sqrt{-\log v}}{(1+v)^2}\,dv \tag{1}$$ but since $$ \int_{0}^{1}v^k \sqrt{-\log v}\,dv = \frac{\sqrt{\pi}}{2(1+k)^{3/2}} \tag{2}$$ by expanding $\frac{1}{(1+v)^2}$ as a Taylor series we get:

$$ I = \frac{1}{\sqrt{2}}\sum_{n\geq 0}(-1)^n (n+1)\frac{\sqrt{\pi}}{2(1+n)^{3/2}} = \color{red}{\frac{\sqrt{\pi}}{2\sqrt{2}}\cdot\eta\left(\frac{1}{2}\right)}\tag{3}$$

and the claim follows from the well-known: $$ \eta(s) = (1-2^{1-s})\,\zeta(s)\tag{4} $$ that gives an analytic continuation for the $\zeta$ function.

  • $\begingroup$ Can you help me understand what substitution you made to get$$\frac 1{2\sqrt2}\int\limits_0^{\infty}du\,\frac {\sqrt u}{\cosh u+1}=\frac 1{\sqrt2}\int\limits_1^{\infty}dv\,\frac {\sqrt{\log v}}{(v+1)^2}$$? $\endgroup$
    – Frank W
    Jun 26 '18 at 23:26
  • $\begingroup$ @FrankW.: $u=\log v$. $\endgroup$ Jun 27 '18 at 12:18


Consider the parametric integral

\begin{equation} I(a) = \int_0^\infty \frac{t^{a-1}}{\cosh^{2} t}\ dt=4 \int_{0}^{\infty} \frac{t^{a-1}}{(e^{t}+e^{-t})^{2}}\ dt = 4 \int_{0}^{\infty}\frac{t^{a-1} e^{-2t}}{(1+e^{-2t})^{2}}\ dt \end{equation}

Hence, your integral is simply

\begin{equation} \int_0^{\infty} \frac{x^2}{\cosh^2x^2}\ dx = -2\ \frac{\partial}{\partial b}\left[\int_0^{ \infty}\frac{t^{a-1}}{1+e^{bt}} \ dt\right]_{a=\frac{1}{2}\ ,\ b=2} \end{equation}

I believe you can evaluate the last expression by your own.


$\newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{\mathrm{i}} \newcommand{\iff}{\Leftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\, #2 \,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$

\begin{align} &\bbox[10px,#ffd]{\int_{0}^{\infty}{x^{2} \over \cosh^{2}\pars{x^{2}}}\,\dd x}\,\,\ \stackrel{x\ \to\ x^{1/2}}{=}\,\,\,\ 2\int_{0}^{\infty}{x^{1/2}\expo{2x} \over \pars{\expo{2x} + 1}^{2}}\,\dd x \\[5mm] = &\ -\int_{x = 0}^{x \to \infty}x^{1/2}\,\dd\pars{{1 \over \expo{2x} + 1}} = \half\int_{0}^{\infty}{x^{-1/2}\expo{-2x} \over 1 + \expo{-2x}}\,\dd x \\[5mm] \stackrel{2x\ \to x}{=}\,\,\,& {\root{2} \over 4}\int_{0}^{\infty}{x^{-1/2}\expo{-x} \over 1 + \expo{-x}}\,\dd x \\[5mm] = & {\root{2} \over 4}\sum_{n = 0}^{\infty}\pars{-1}^{n} \int_{0}^{\infty}x^{-1/2}\expo{-\pars{n + 1}x}\,\dd x \\[3mm] \stackrel{\pars{n + 1}x\ \to x}{=}\,\,\,& {\root{2} \over 4}\sum_{n = 0}^{\infty} {\pars{-1}^{n} \over \pars{n + 1}^{1/2}}\ \overbrace{% \int_{0}^{\infty}x^{-1/2}\expo{-x}\,\dd x}^{\ds{\Gamma\pars{\half}\ =\ \root{\pi}}} \\[5mm] = &\ {\root{2} \over 4}\,\root{\pi}\sum_{n = 1}^{\infty}{\pars{-1}^{n + 1} \over n^{1/2}} \end{align}

With the identity $\ds{\sum_{n = 1}^{\infty}{\pars{-1}^{n + 1} \over n^{s}} = \pars{1 - 2^{1 - s}}\zeta\pars{s}}$: \begin{align} \bbox[#ffd,10px]{\int_{0}^{\infty}{x^{2} \over \cosh^{2}\pars{x^{2}}}\,\dd x} & = {\root{2} \over 4}\,\root{\pi}\pars{1 - 2^{1 - 1/2}}\zeta\pars{\half} \\[5mm] & = \bbox[10px,border:1px groove navy]{{\root{2} - 2 \over 4}\,\root{\pi}\zeta\pars{\half}} \approx 0.3791 \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.